1975
DOI: 10.1177/028418517501600506
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Disturbances following Missile Wounding of Soft Tissue

Abstract: The early circulatory changes following high velocity missile wounding to soft tissue of an extremity were analysed by hemodynamic methods and serial angiography. The extent of the tissue injury and the functional disturbances were mapped out and the time-course of the alterations in blood flow was registered. Possible mechanisms for the observed abnormalities are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In zones C and D a significant increase in creatine phosphate in comparison to control muscle tissue was observed in the penicillin-treated animals. This could be due to the early hyperemia in these zones as found in isotope and angiographic studies [26,32], possibly in combination with a pro tective effect of penicillin G against progres sive bacterial invasion [13].…”
Section: Discussionmentioning
confidence: 99%
“…In zones C and D a significant increase in creatine phosphate in comparison to control muscle tissue was observed in the penicillin-treated animals. This could be due to the early hyperemia in these zones as found in isotope and angiographic studies [26,32], possibly in combination with a pro tective effect of penicillin G against progres sive bacterial invasion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally it has been shown that both highenergy violence, as exemplified by missile wounding [21,27] as well as low energy violence by contusion trauma, is followed by an immediate in crease of blood flow and a marked vasodilatation in the traumatized ex tremity [19,20,29]. This regional hemodynamic reaction seems to de pend for the most part on the damage to the soft tissues.…”
mentioning
confidence: 99%